Bicycling to Work and Primordial Prevention of Cardiovascular Risk: A Cohort Study Among Swedish Men and Women. Issue 11 (November 2016) - Grøntved, Anders; Koivula, Robert W.; Johansson, Ingegerd; Wennberg, Patrik; Østergaard, Lars; Hallmans, Göran; Renström, Frida; Franks, Paul W.
Abstract : Background: Bicycling to work may be a viable approach for achieving physical activity that provides cardiovascular health benefits. In this study we investigated the relationship of bicycling to work with incidence of obesity, hypertension, hypertriglyceridemia, and impaired glucose tolerance across a decade of follow‐up in middle‐aged men and women. Methods and Results: We followed 23 732 Swedish men and women with a mean age of 43.5 years at baseline who attended a health examination twice during a 10‐year period (1990–2011). In multivariable adjusted models we calculated the odds of incident obesity, hypertension, hypertriglyceridemia, and impaired glucose tolerance, comparing individuals who commuted to work by bicycle with those who used passive modes of transportation. We also examined the relationship of change in commuting mode with incidence of these clinical risk factors. Cycling to work at baseline was associated with lower odds of incident obesity (odds ratio [OR]=0.85, 95% CI 0.73–0.99), hypertension (OR=0.87, 95% CI 0.79–0.95), hypertriglyceridemia (OR=0.85, 95% CI 0.76–0.94), and impaired glucose tolerance (OR=0.88, 95% CI 0.80–0.96) compared with passive travel after adjusting for putative confounding factors. Participants who maintained or began bicycling to work during follow‐up had lower odds of obesity (OR=0.61, 95% CI 0.50–0.73), hypertension (OR=0.89, 95% CI 0.80–0.98), hypertriglyceridemia (OR=0.80, 95% CI 0.70–0.90), and impaired glucose tolerance (OR=0.82, 95% CI 0.74–0.91) compared with participants not cycling to work at both times points or who switched from cycling to other modes of transport during follow‐up. Conclusions: These data suggest that commuting by bicycle to work is an important strategy for primordial prevention of clinical cardiovascular risk factors among middle‐aged men and women.